Impact of epidemiological factors on the prevalence, intensity and distribution of ectoparasites in pigeons - Ahmed, Haroon; Naz, Mehmoona; Mustafa, Irfan; Khan, Mobushir Riaz; Asif, Saira; Afzal, Muhammad Sohail; Simsek, Sami (Springer India, 2017)
This study was carried out on domestic pigeons (Columba livia domestica) from September (2014) to June (2015) to determine the prevalence, intensity and species of ectoparasites in Sargodha region, east of Pakistan. A total of 200 domestic pigeons were inspected from the study area. Parasites were collected by forceps and stored in 70% ethanol. The epidemiological information e.g. health condition, color of plumage, mode of living, breed, intensity etc. were recorded in the form of questionnaire. The overall prevalence of ectoparasites in pigeon was 90.5% (181/200). Of the total of 200 (83 males and 117 females) domestic pigeons inspected, 73 (87.95%) and 108 (92.30%) were infected, respectively. The ectoparasites spp. were identified as Columbicola columbae (Linnaeus, 1758) and Colpocephalum turbinatum (Denny, 1842). The Qasid breed showed highest infestation rate (91.25%) as compared to other two observed breeds. Pigeon of white color were more infested (91%) as compared to other colors. Thus color and breed factors showing the random differences. In medicated birds the rate of infestation of ectoparasites was 87% reflecting that drugs are unable to control or might be due to resistance. There was significant difference between the number of parasites on tail, neck, chest and wings within different breeds, as well as in the months. The mean intensity of parasites was in urban areas (28.5), rural areas (14.98), and sub-rural areas (23.55). In conclusion the prevalence of ectoparasites in pigeons is very high in north-east region of Pakistan. © 2017, Indian Society for Parasitology.
Keywords: Colpocephalum turbinatum; Columbicola columbae; Domestic pigeon; Ectoparasites; Epidemiological factors